2016
DOI: 10.1007/s10695-016-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism-related gene expression pattern of Atlantic bluefin tuna (Thunnus thynnus L.) larvae fed on live prey

Abstract: The present study is the first to evaluate lipid metabolism in first-feeding Atlantic bluefin tuna (ABT; Thunnus thynnus L.) larvae fed different live prey including enriched rotifers Brachionus plicatilis and Acartia sp. copepod nauplii from 2 days after hatch. Understanding the molecular basis of lipid metabolism and regulation in ABT will provide insights to optimize diet formulations for this high-value species new to aquaculture. To this end, we investigated the effect of dietary lipid on whole larvae lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 99 publications
(117 reference statements)
6
18
0
Order By: Relevance
“…Moreover, low swimbladder inflation rates, surface and sinking deaths, dispersed sizes, malformations and tank wall collisions are common issues, not only in ABT culture, but also in other tuna species (Sawada et al, 2005;Yasunori, 2012). Initial data related to the feeding sequence of ABT larvae suggested that mortality observed during the first stages of life could be due partly to nutritional deficiencies (De La Gandara et al, 2010;Partridge, 2013;Betancor et al, 2016). In this respect, researchers have described three critical periods of mortality in Pacific bluefin tuna larvae: the first during the initial 10 days after hatching (dah), the second between 14 and 30 dah, and the third from 30 to 60 dah (Partridge, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low swimbladder inflation rates, surface and sinking deaths, dispersed sizes, malformations and tank wall collisions are common issues, not only in ABT culture, but also in other tuna species (Sawada et al, 2005;Yasunori, 2012). Initial data related to the feeding sequence of ABT larvae suggested that mortality observed during the first stages of life could be due partly to nutritional deficiencies (De La Gandara et al, 2010;Partridge, 2013;Betancor et al, 2016). In this respect, researchers have described three critical periods of mortality in Pacific bluefin tuna larvae: the first during the initial 10 days after hatching (dah), the second between 14 and 30 dah, and the third from 30 to 60 dah (Partridge, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, omega 3 (n-3) LC-PUFA, such as eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; 22:6n-3), are required by most marine fish and are essential fatty acids for survival, normal growth and development (Tocher, 2010). There has been considerable research interest in the key enzymes of the LC-PUFA biosynthetic pathway, fatty acyl desaturases (Fads) and elongases of very long chain fatty acids (Elovl) in fish species including tuna (Gregory et al, 2010;Morais et al, 2011;Betancor et al, 2016). Furthermore, the capacity for endogenous synthesis of EPA and DHA is limited in ABT and so the lipid biochemistry underpinning the high tissue DHA and DHA/EPA ratio is unclear (Gregory et al, 2010;Morais et al, 2011;Scholefield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, fatty‐acid components of three tuna species in the Nansei area and two nursery areas of bluefin tuna were significantly different. The HUFA composition of reared Atlantic bluefin tuna larvae tended to reflect their dietary composition (Betancor et al, ; Ortega and Mourente, ). In the field, previous studies reported the different feeding habits among two tunas and skipjack tuna (Kodama et al, ; Uotani et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in rainbow trout alevins during the shift from endogenous to exogenous feeding show that the expression of genes encoding the lipolytic enzymes CPT1A and CPT1B decreases as ontogeny proceeds, a result consistent with the progressive switch from the utilization of lipid reserves in endogenously feeding fry to the use of exogenous feeds (Mennigen, Skiba‐Cassy, & Panserat, ). Additionally, studies in Atlantic bluefin tuna ( Thunnus crocea , Linnaeus 1758) focused on first‐feeding larvae fed different live prey show differences in the expression patterns of genes encoding lipid metabolism enzymes (including FAS and CPT1) related to prey type, which were attributed to differences in lipid and FA composition of prey (Betancor, Ortega, Gándara, Tocher, & Mourente, ).…”
Section: Discussionmentioning
confidence: 99%